Les dispositifs individualisés d'aide aux élèves : lieux de renormalisation. Comparaison entre l'Ontario et la Belgique - Nathalie Bélanger; Sabine Kahn (Nantes Université, 2019)
Individualized student support is becoming more and more used in schools around the world. Individual Learning Plans (IAPs) in Belgium or Individual Education Plans (IEPs) in Ontario are examples of those kind of support. Can they be considered as places of renormalization and reinterpretation of the school norm? They are analyzed here as devices from a socio-material and normative approach of activity. The results show that the prescribed plan can be associated with a paradigm shift that aims to guide school professionals towards new norms. While the real plans reveal, in both contexts, the renormalizations at work but also the persistence of professional cultures still little acquired with the new injunctions and the norms which underlie them.